A novel methodology to characterize LGA packaged GaN power transistors using a mother/daughter board configuration for the reliability qualification in the mild hybrid applications. (November 2022) - Douzi, Chawki; Kadi, Moncef; Dherbecourt, Pascal; Besserour, Mohamed Akram; Joubert, Eric; Fouquet, François
Abstract: The Gallium Nitride GaN based power switching device EPC2206 has a Land Grid Array (LGA) packaging with a pitch between pads of 400 μm. This low pitch does not facilitate transistor connection on a test vehicle in the context of aging tests where the component must undergo repetitive sequences of I(V) and C(V) characterizations, threshold voltage, leakage currents and then repetitive stress. Thus, the purpose of this paper is to adapt this encapsulated power switching device for coaxial or coplanar type measurements and to look for the best configuration to move this transistor from one test bench to another by using an adaptation system on a printed circuit board (PCB). To choose the best performances of three adaptation system configurations, this paper presents, on the one hand, an experimental study on I(V) characterization, threshold voltage Vth, drain leakage current Idss, gate leakage current Igss. On the other hand, a series of measurements of these different characteristics was carried out on the three EPC2206 connection configurations to validate the reproducibility of the measurements. Highlights: Experimental investigation are presented and analyzed. Adaptation LGA packaged power GaN switching device EPC2206 for coaxial or coplanar type measurements Comparison between 3 configurations to choose the best one in terms of reproducibility of results Validation of the chosen configuration by the reproducibility of some electrical parameters such as I(V), Vth, Igss and Idss